To be or not to be. Death as a metaphoric dimension in children’s literature - Grilli, Giorgia (Rivista di Storia dell’Educazione, 2017)
In the history of children’s literature, in Italy as elsewhere, when we take into consideration the so-called “classics” or, in more recent times, the titles and authors most appreciated by readers and critics alike, we find out that there is an undeniable – if implicit, metaphoric, subterranean – theme, recurring through their pages: death. Aim of this exploration, characterized by a comparative approach, is to try and understand why death is a Leitmotiv in the best children’s literature of all times, in Italy as in the rest of the Western world, and what is actually meant by the recurrent, metaphorical allusion to this dimension in children’s books.